Being brown : Sonia Sotomayor and the Latino question - Lima, Lázaro (American studies now, 2020)
"Sonia Sotomayor is the highest ranking Latino/a in the United States. Her story of accomplishment and rise to the pinnacle of American public life seemed to herald a profound cultural and historical shift. Latinos are America's largest minority and also its most disenfranchised. For many, Sotomayor's ascent represented the elusive fulfillment of an American dream. A chronological narrative of her extraordinary life, Being Brown juxtaposes Sotomayor's phenomenal successes with the twists and turns of minority inclusion in American democracy. Lázaro Lima also shows how Sotomayor's own self-making as a Puerto Rican model of possibility allows us to understand not only the appeal but also the limits of representation. Culling through Sotomayor's own writings, her Supreme Court dissents, and speeches, Lima questions what it means to have a powerful Latina in the Supreme Court. What does her ascent say about social mobility and inclusion? While Sotomayor's story inspires hope, it also reveals much about the general lack of equality of Latinos and other disenfranchised communities"--Provided by publisher.